Delimitação de corredor ecológico utilizando ferramentas geotecnológicas - Mardeni, Vinícius Duarte Nader (2023)
Ecological corridors work as a viable way of mitigating the environmental impact arising from forest fragmentation, through the interconnectivity of forest fragments, using different techniques. In this context, the objective of this study is to propose a route for the implementation of an ecological corridor in the Itapemirim river basin. The specific objectives were: (i) to delimit the permanent preservation areas of the Itapemirim river basin and compare the use and land cover in the delimited areas; calculate the landscape ecology indices and select the forest fragments with the greatest potential for the implementation of ecological corridors using fuzzy logic; assess costs and outline the best route for implementing the ecological corridor, considering distance and physical impediments; assess land costs and expropriation costs to delimit the ecological corridor in the study area. In order to carry out the mapping of land use and land cover, the MapBiomas platform was used, based on Landsat 8 satellite images. The Permanent Preservation areas were delimited according to criteria established by Law No. which provides for APP parameters, definitions and limits. The characterization and structural quantification of some of the landscape ecology indices were carried out using the computational application QGIS 3.26, through the plugin LecoS 3.0.1 and Fragstats 4.2. The connected forest fragments were the Caparaó National Park, the Serra das Torres State Natural Monument and the fragments selected through the application of fuzzy logic to the landscape ecology indices (LEI). The proposed ecological corridor was delimited according to the lowest cost route, considering: land use and land cover, permanent preservation areas, fragment potential, slope and subnormal agglomerations. For each cost matrix image, their respective statistical weights were calculated using the hierarchical method - Analytic Hierarchy Process - AHP, as well as for the analysis of priority areas for forest recovery, considering: land use and cover, areas of permanent preservation, pedology, lithology and biological importance. The Interconnection between the protected areas and the fragments with the ecological corrector followed the orientation described by CONAMA nº 09/96. Based on the development of the work, the following results are identified: the largest class of land use and land cover is pasture. Of the area destined for permanent preservation, 68.58% is in conflict with what is established by law. The VTN per hectare of the pasture class is the second largest among the values of VTN per UCT, representing 64.28% of the total. The map of priority areas indicated that 31.86% of the area was classified as an area of very high or high importance and 42.97% as low or very low priority for forest recovery. Thus, it is concluded that the least cost path algorithm associated with the result generated by the multicriteria decision method (AHP), constitutes an important tool for the planning and implementation of an ecological network because it takes into account primary factors the decision-making of the location of the best route.